Exenatide and Metformin Improve Serum Indices and Intestinal Flora in patients with Type 2 Diabetes Mellitus and Non-Alcoholic Fatty Liver Disease - Jiang, Xiaojie; Shi, Tingting; Han, Dan; Chen, Juan (Journal of the Pakistan Medical Association, 2023)
The aim of the study was to investigate the influence of Exenatide combined with Metformin on fasting blood glucose, postprandial glucose, triglycerides, total cholesterol, alanine aminotransferase, aspartate aminotransferase, and intestinal flora in type 2 diabetes mellitus cases with non-alcoholic fatty liver disease. A total of 128 type 2 diabetes mellitus patients with non-alcoholic fatty liver disease, diagnosed from January 2019 to January 2022, were included and randomly assigned to either Group A (n=64) or Group B (n=64). Group A received Metformin, while Group B received Exenatide injection and Metformin. After 24 weeks of treatment, blood glucose indices (fasting blood glucose and postprandial glucose), blood lipid indices (triglycerides and total cholesterol), liver function indices (alanine aminotransferase and aspartate aminotransferase) were all lower in Group B than in Group A (P < 0.001 for all). —Continue